Sifat Fisis dan Mekanis Papan Lamina dari Limbah Kayu Ulin (Eusideroxylon zwageri) dan Kayu Meranti Merah (Shorea leprosula Miq.): Physical and Mechanical Properties of Laminated Wood from Ironwood (Eusideroxylon zwageri) and Red Meranti (Shorea leprosula Miq.) Waste - Eva Nurmarini; Taman Alex; Salfinus; Risna Nona; Agung Nugrawan Kutana (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
The timber industry is growing with increasing demand for wood raw materials, driving innovations such as lamination. This study aims to determine the physical and mechanical properties of laminated boards made from a combination of ironwood (Eusideroxylon zwageri) and red meranti (Shorea leprosula) wood waste. The laminated boards were arranged in four combination treatments, namely MUM (Meranti-Ironwood-Meranti), MMM (Meranti-Meranti-Meranti), UMU (Ironwood-Meranti-Ironwood), and UUU (Ironwood-Ironwood-Ironwood), using PVAc adhesive with a pressing pressure of 8-9 bar for one hour. Testing was conducted on moisture content, density, Modulus of Elasticity (MoE), and Modulus of Rupture (MoR). The results showed that the moisture content of the laminated boards ranged from 13.52–17.32% and fell within the equilibrium moisture content range for tropical wood. The density values ranged from 0.54–0.94 g/cm³, with the highest value in ironwood and the lowest in red meranti wood. The MoE values ranged from 86,180 to 179,939 kgf/cm², and all variations met the JAS (2007) standard. The MoR values ranged from 754 to 1,512 kgf/cm², which also complied with the JAS breaking strength standard (≥300 kgf/cm²). The combination of ironwood and red meranti wood waste produced laminated boards with good performance and potential as an alternative sustainable construction material.